Traffic Patterns and Emergency Medical Services Prenotification Transport Estimates in Trauma Activations [Response to Letter] - Gorgens S; Klein EN; Bank MA; Jafari D (Open Access Emergency Medicine)
Sophia Gorgens,1 Eric N Klein,2,3 Matthew A Bank,2,3 Daniel Jafari1,3 1Department of Emergency Medicine, Northwell Health, Long Island, NY, USA; 2Department of Surgery, Northwell Health, Long Island, NY, USA; 3Zucker School of Medicine at Hofstra, Long Island, NY, USACorrespondence: Sophia Gorgens, Department of Emergency Medicine, Northwell Health, 300 Community Drive, Manhasset, NY, 11030, USA, Email sophia.gorgens@gmail.com